The design, development and validation of work-based surface anatomy teaching (WSAT) model and its efficacy on students’ learning competencies - Bakar, Yasrul Izad Abu (2024)
Surface anatomy is a subdiscipline of anatomy that helps medical students to learn and perform physical examination and clinical procedures safely. However, surface anatomy education is less emphasised in the medical curricula, and there is insufficient empirical evidence to support the effectiveness of surface anatomy teaching in higher education. The goal of this study is to create a valid and effective work-based surface anatomy teaching model based on two scoping review findings. The content, response process, and internal validity of the Work-based Surface Anatomy Teaching (WSAT) model were established through expert ratings. A small-scale randomised-controlled trial with 28 participants was carried out. The control group received routine surface anatomy instruction, whereas the intervention group received the WSAT instruction. Pre- and post-teaching assessments, as well as reflective writing and follow-up sessions, were used to assess knowledge retention and learning competencies change. In comparison to the control group, the intervention group demonstrated significantly lower extraneous load, higher self-perceived learning, and higher cognitive and physical engagement. Despite having similar baseline surface competencies, the intervention group outperformed the control group in cognitive, psychomotor, and affective competency acquisition, as well as retention of psychomotor skills and professional behaviour. Positive student experiences with the WSAT instruction were revealed through qualitative analysis. While the WSAT model produced positive results, the impact of the instruction on students' behaviours and organisation should be assessed in future studies. In essence, teaching surface anatomy in a workplace setting can be successful by utilizing the evidence-based WSAT model and framework. While acknowledging the study's limitations and the need for future larger randomised controlled trials (RCTs), educators should still consider incorporating the WSAT model into their teaching practises. Engaging in such activities can improve students' comprehension of anatomy and foster greater engagement in surface anatomy learning.